Optical-response properties in an atom-assisted optomechanical system with a mechanical pump. (28th April 2017) - Sun, Xue-Jian; Chen, Hao; Liu, Wen-Xiao; Li, Hong-Rong
Abstract: We investigate the optical-response properties of a coherent-mechanical pumped optomechanical system (OMS) coupled to a Λ-type three-level atomic ensemble. Due to the optomechanical and the cavity-atom couplings, the optomechanically induced transparency (OMIT) and electromagnetically induced transparency (EIT) phenomena could both be observed from our proposal. In the presence of a coherent mechanical pump, we show that the OMIT behavior of the probe field exhibits a phase-dependent effect, leading to the switch from OMIT to optomechanically induced absorption or amplification, while the feature of EIT remains unchanged. The distinctly different effects of the mechanical pump on OMIT and EIT behavior assure us that the absorption (amplification) and transparency of the output probe field can be simultaneously observed. Moreover, a tunable switch from slow to fast light can also be realized by tuning the phase and amplitude of the mechanical pump. In particular, the presence of the atomic ensemble can further adjust the group delay, providing additional flexibility for achieving the tunable switch.